2015
DOI: 10.1016/j.amsu.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the high risk emergency surgical patient: Which risk prediction model should be used?

Abstract: IntroductionNational guidance states that all patients having emergency surgery should have a mortality risk assessment calculated on admission so that the ‘high risk’ patient can receive the appropriate seniority and level of care. We aimed to assess if peri-operative risk scoring tools could accurately calculate mortality and morbidity risk.MethodsMortality risk scores for 86 consecutive emergency laparotomies, were calculated using pre-operative (ASA, Lee index) and post-operative (POSSUM, P-POSSUM and CR-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…Some employ the same variables we selected[ 5 7 ] but have limited generalizability and are not easily applied at the bedside. Others, such as the POSSUM score, rely on multiple pre and intraoperative variables and have been shown to overestimate mortality in lower-risk groups [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some employ the same variables we selected[ 5 7 ] but have limited generalizability and are not easily applied at the bedside. Others, such as the POSSUM score, rely on multiple pre and intraoperative variables and have been shown to overestimate mortality in lower-risk groups [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several adjustments have been made to combat the overestimation of risk by the POSSUM score such as the Portsmouth modification. [7][8][9] More recently, a novel risk prediction calculator has been developed by the NELA network which is designed for EL. 10 The calculator is certainly specific and modern but is based on the definitions of comorbidities and factors collected for the older P-POSSUM calculator.…”
Section: Introductionmentioning
confidence: 99%
“…4e7 Various models are available to estimate the short-term risk of death after emergency bowel surgery, including: the Portsmouth Physiological and Operative Severity Score for the enumeration of Mortality and Morbidity (P-POSSUM) model, 8e12 the Biochemistry and Haematology Outcome Model (BHOM), 13 the Surgical Outcome Risk Tool (SORT), 14 and others. 3,15e24 Systematic reviews 25,26 of such models have identified substantial limitations in their design because they were often derived using small, single-site studies, were restricted to specific populations, or both. This makes it difficult to draw general conclusions about their performance.…”
mentioning
confidence: 99%